ANALISIS KARAKTER TOKOH UTAMA DALAM NOVEL LINTANG GUMEBYAR KARYA INDARPATI (Tinjauan Psikologi Sastra) - Erlina Erlina (Ensiklopedia Education Review, 2022)
This research is motivated by the analysis of the main characters in Lintang Gumebiyar novel by Indarpati (psychology literature review). Character is an attitude, emotions and actions character created by author distinguishes it from the other figures. Ways of expressing the character can be seen through a direct statement, speech or action figures. This study aimed to describe the main characters in Lintang Gumebiyar novel by Indarpati terms of the psychology literature. The research is a qualitative study using descriptive methods. The object of this research is the analysis of the main characters in Lintang Gumebiyar novel by Indarpati. Sources of data in this study is  Lintang Gumebiyar novel by Indarpati consisting of 245 pages divided into 13 episodes. Data collection techniques in this research is through the secondary source that is documentation, by: (1) read repeatedly Lintang Gumebiyar novel by Indarpati, (2) provide the coding on the Lintang Gumebiyar novel by Indarpati about the actions taken main character, because the main character do an actions, and as a result of the actions of the main character, (3) records the data that has been coded, and (4) present descriptive data. While the steps in analyzing data are: (1) read all the data that has been collected, (2) classify the data that has been coded by their groups according the table instrument, (3) conduct analysis and discussion by analyzing the characters in the data, and (4) formulate conclusions and suggestions. The results of this study indicate that the main character in Lintang Gumebiyar novel by Indarpati has two characters that are good (protagonist) and bad (antagonist) which is determined by the norms in society.Keywords: character, the main character, novel, literary psychology.